IS THERE ANY IMPACT OF SOCIAL MEDIA ON ACADEMIC PERFORMANCE? (An Empirical Study From College Student In Jakarta) - Nurcahyo, Bagus (UNIVERSITAS NUSANTARA PGRI KEDIRI, 2017)
This study aimed to examine empirically the social network activities that affect academic performance. Obtain sample data using questionnaires and obtain data from top 10 universities in Webometrics and total 75 respondents. This study examined the utilization period of social networks, social network usage motivation, academic data and activities respondents perceived influence on academic performance. Using multiple regression techniques, the study found that social network activity does not negatively impact on academic performance. Keywords: social network, Facebook, Twitter, Academic Performance, GPA